Local cerebral glucose utilization in monkeys with hemiparkinsonism induced by intracarotid infusion of the neurotoxin MPTP - Palombo, E (J Neurosci, 1990)
Quantitative 2-[14C]deoxyglucose autoradiography was used to map the pattern of alterations in local cerebral glucose utilization associated with unilateral lesions of the substantia nigra pars compacta produced by the infusion of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) into one internal carotid artery of rhesus monkeys. These monkeys become hemiparkinsonian, displaying rigidity, bradykinesia, and tremor of the limbs contralateral to the side of MPTP infusion; during spontaneous activity they turn toward the side of the lesion. Eighty- two brain areas were examined, and statistically significant metabolic changes were confined mainly to basal ganglia structures ipsilateral to the side of the lesion. Glucose utilization was reduced in the substantia nigra pars compacta and ventral tegmental area, i.e., in the areas of cell loss. Increases in glucose utilization in regions normally innervated by the lesioned area were observed in the post- commissural portions of the putamen and dorsolateral caudate. Other structures showing statistically significant metabolic changes were the external segment of the globus pallidus (+40%), subthalamic nucleus (- 17%), and pedunculopontine nucleus (+15%). There were also smaller changes in portions of the thalamus (ventral anterior nucleus, parafascicular nucleus) and premotor cortex. All significant metabolic changes were confined to the side of the substantia nigra lesion and were essentially restricted to regions involved in the production of movement or maintenance of posture.